EXTH-18. PEPTIDE NANO-STRUCTURES ENHANCE PEDIATRIC BRAIN TUMOR CHEMOTHERAPEUTIC EFFICACY. (11th November 2019) - XI, Guifa; Mahenthiran, Ashorne; Best, Benjamin; Nayak, Sonali; Smith, Cara; McClendon, Mark; Mania-Farnell, Barbara; Kessler, John; James, Charles; Stupp, Samuel; Tomita, Tadanori
Abstract: Pediatric gliomas, particularly high-grade gliomas, which include diffuse intrinsic pontine gliomas (DIPGs), are among the most formidable and devastating cancers in children. These tumors remain incurable, despite many treatment approaches. We recently identified a small population of glioma cells with stem-like features in pediatric gliomas (glioma stem cells: GSCs), that may be responsible, for therapeutic resistance. Bone morphogenetic protein 4 (BMP4), essential for CNS development, increases GSC therapeutic sensitivity and is a promising adjuvant for glioma treatment. Mechanisms through which BMP4 increases therapeutic sensitivity need to be elucidated, as this can lead to identification of additional treatment targets and delivery systems for BMP4 administration in a clinical setting. Additionally, extension of BMP4 short half-life would enhance its' clinical application. Here we show that BMP4 increases chemosensitivity by decreasing H3K4me3 at the promoter of multidrug resistant gene 1 (MDR1), resulting in decreased MDR1 expression. BMP4 appears to bring about this effect by decreasing hSETD1A, an H3K4me3 methyltransferase. Our work also demonstrates the first use of a novel sulfated glycopeptide (glyco-PA) nanostructure as a vector for BMP4 delivery. Glyco-PA markedly extended and enhanced BMP4 function, and increased chemotherapeutic anti-tumor activity against pediatric malignant glioma cells in culture. Overall, this work illuminates BMP4 effects on pediatric glioma therapeutic sensitivity through epigenetic mechanisms, and demonstrates the potential of bioactive glyco-PA nanostructures as a delivery mechanism for treating pediatric malignant gliomas and other tumors.